STUDI MENGENAI BRAND COMMUNICATION, BRAND IMAGE DAN BRAND TRUST SERTA PENGARUHNYA TERHADAP BRAND LOYALTY PADA PRODUK HAND AND BODY LOTION MEREK CITRA - Nurdianasari, Rista; Indriani, Farida (Diponegoro Journal of Management, 2017)
Brand loyalty is a major element of an industry to achieve competitive advantages. The existence of brand loyalty help the company to reduce marketing costs and maximize revenue. The main focus of this research is the issue that the brand loyalty of Hand and Body Lotion Citra continues to decline. Indications of brand loyalty can be seen from the percentage of brand share and brand value. The purpose of this research is to analyze the indirect effect of brand communication toward brand loyalty of Hand and Body Lotion Citra trough brand image and brand trust as the intervening variable.The sampling method used in this research is non-probability sampling with purposive sampling technique. Samples were collected from 100 female with age 15-35 years old in Semarang who always use Hand and Body Lotion Citra. Collected data were analyzed with several tests, such as: validity test, reliability test, classical assumption test, multiple linear regression test, goodness of fit test using IBM SPSS 23 for windows and sobel test.The result showed in the classical testing assumption, the regression model is normally distribution and heteroscedasticity does not occur. This research explain the relationship of brand communication has a positive significant effect on brand loyalty through brand trust as intervening variable. The results of research also indicate that relationship between brand communication on brand loyalty becomes stronger when mediated with brand image and brand trust variables simultaneously.